The position of women in Ancient Rome: transformation from paganism to christianity - Добровольська, К.; Рома, А. (Київський національний університет імені Тараса Шевченка, 2024)
The religious milieu of ancient Rome was a complex canvas, deeply interwoven with the lives of its inhabitants, both men and women. This article delves into the intricate web of religious influence on women's lives in ancient Rome, with a particular focus on the divergent impacts of paganism and Christianity. Through a meticulous examination of sources, this exploration seeks to illuminate the lives of Roman women and the roles they played within these religious traditions, the constraints they faced, and the transformative shifts that occurred as Rome transitioned from paganism to Christianity. By dissecting the intersections of faith, gender, and social dynamics, this article offers a nuanced understanding of the evolving religious landscapes and their implications for women in antiquity. In the light of the growing interest in the history of Roman paganism and early Christianity, the relevance of the study is determined by the need to present a more complete socio-cultural and religious picture of that time. The innovation of the study lies in a holistic, comprehensive analysis of the issues raised by highlighting the transformation of the position of women from paganism to Christianity. The analysis is carried out through the prism of feminist issues related to religion, as well as the legal and social nature of the religious life of the ancient Romans. Moreover, such a religious analysis of women's issues in Ancient Rome, in particular in domestic studies, has not yet been sufficiently developed and presented in Ukrainian scientific discourse. This study is based on a synthesis of historical, analytical, and comparative methods. The study is based on the works of Mary Beard, Bonnie McLachlan, Maureen Fant, Mary Lefkowitz, Celia Schultz, Nicole Boelz-Janssen, Ariadne Staples, Richard Bauman, Enzo Bianchi, Anne-Marie Pelletier, and others. Among domestic researchers, we can single out Natalia Chukhym and Olga Gomilko.

Релігійне середовище Давнього Риму являло собою складну канву, глибоко переплетену з життям своїх мешканців, як чоловіків, так і жінок. Розглянуто складну систему релігійного впливу на життя жінок у Давньому Римі, зокрема, впливу язичництва та християнства. Ґрунтуючись на ретельному вивченні джерел, це дослідження являє собою спробу показати становище римських жінок та їхніх ролей у межах зазначених релігійних традицій, обмежень, з якими вони стикались, та трансформацій, які відбулись під час переходу Риму від язичництва до християнства. Сформульовано, як на перетині віри, гендера та соціальної динаміки з'явилося розуміння нюансів мінливості релігійних ландшафтів та їх наслідків для жінок давнини. Актуальність дослідження зумовлена необхідністю подання більш повної соціокультурної та релігійної картини того часу у світлі зростання цікавості до історії римського язичництва та раннього християнства. Зроблено цілісний, всебічний аналіз піднятої проблематики шляхом висвітлення питання трансформації становища жінки від язичництва до християнства. Аналіз здійснено через призму дотичних до релігії проблем феміністичного спрямування, а також правового та соціального характеру релігійної дійсності давніх римлян. Подібний релігієзнавчий аналіз жіночої проблематики в Давньому Римі, зокрема у вітчизняних дослідженнях, досі не був достатньо розроблений та пред- ставлений в українському науковому дискурсі. Це дослідження ґрунтується на синтезі історико-аналітичного та компаративного методів, базується на працях Мері Бірд, Бонні Маклахлан, Морін Фант, Мері Лефковіц, Сілії Шульц, Ніколь Боельц-Янссен, Аріадни Стейплс, Річарда Баумана, Енцо Б'янкі, Анн-Марі Пелетьє та інших. Серед вітчизняних дослідників можна виокремити Наталію Чухим, Ольгу Гомілко.
Становище жінки в давньому Римі: трансформації від язичництва до християнства
Keywords: Roman religion; feminism; religious identification; Christianity; римська релігія; фемінізм; релігійна ідентифікація; християнство